ANALYSIS OF STUDENT'S ISLAMIC RELIGION EDUCATION LEARNING OUTCOMES USING THE INQUIRY LEARNING MODEL IN THE INDEPENDENT CURRICULUM - Komarudin; Al Ayyubi, Ibnu Imam; Yasmin, Sabrina; Annatasya, Tiara; Muhaemin, Abdul (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2024)
This study aims to analyze whether or not there is a difference between student learning outcomes using the inquiry model in Islamic Religion Education learning based on the origin of the student’s school towards the implementation of an independent curriculum in their school. This research was conducted at SMPN 1 Cisarua, SMPN 2 Parongpong, and SMPN 2 Ciampel with a quantitative research approach. This research method uses the survey method and Analysis of Variance test analysis with a sample of 33 students at SMPN 1 Cisarua, 35 students at SMPN 2 Parongpong, and 38 students at SMPN 2 Ciampel with a total of 106 students in inferential statistical analysis. In this study, it was found that there were differences between student learning outcomes in Islamic Religion Education using the inquiry learning model at SMPN 1 Cisarua, SMPN 2 Parongpong, and SMPN 2 Ciampel. The differences that occur among the three schools occur in SMPN 1 Cisarua with SMPN 2 Parongpong and SMPN 2 Parongpong with SMPN 2 Ciampel. Meanwhile, SMPN 1 Cisarua and SMPN 2 Ciampel have no difference. Thus, further research is expected that can be done by testing the Analysis of Variance to see the differences and interactions that occur between student learning outcomes based on school origin and gender.